Dehydration and persistence hunting in Homo erectus. Issue 138 (January 2020) - Hora, Martin; Pontzer, Herman; Wall-Scheffler, Cara M.; Sládek, Vladimír
Abstract: Persistence hunting has been suggested to be a key strategy for meat acquisition in Homo erectus . However, prolonged locomotion in hot conditions is associated with considerable water losses due to sweating. Consequently, dehydration has been proposed to be a critical limiting factor, effectively curtailing the usefulness of persistence hunting prior to the invention of water containers. In this study, we aimed to determine the extent to which dehydration limited persistence hunting in H. erectus . We simulated ambient conditions and spatiotemporal characteristics of nine previously reported persistence hunts in the Kalahari. We used a newly developed and validated heat exchange model to estimate the water loss in H. erectus and a recent Kalahari hunter. Water loss equivalent to 10% of the hunter's body mass was considered the physiological limit of a hunt with no drinking. Our criterion for ruling dehydration out of being a limit for persistence hunting was the ability to hunt without drinking for at least 5 h, as this was the longest duration reported for a successful persistence hunt of large prey. Our results showed that H. erectus would reach the dehydration limit in 5.5–5.7 h of persistence hunting at the reported Kalahari conditions, which we argue represent a conservative model also for Early Pleistocene East Africa. Maximum hunt duration without drinking was negatively related to the relative body surface area of the hunter. Moreover, H. erectus would be able to persistence hunt over 5 h without drinking despite possible deviations from modern-like heat dissipation capacity, aerobic capacity, and locomotor economy. We conclude that H. erectus could persistence hunt large prey without the need to carry water.